Initial PCV Chemotherapy Followed by Radiotherapy Is Associated With a Prolonged Response But Late Neurotoxicity in 20 Diffuse Low-Grade Glioma Patients - Blonski, Marie; Obara, Tiphaine; Brzenczek, Cyril; Pouget, Celso; Dillier, Céline; Meyer, Mylène; Lavigne, Laura; Forthoffer, Natacha; Broussois, Aurélie; Gauchotte, Guillaume; Baron, Marie-Hélène; Rech, Fabien; et al. (Frontiers in Oncology, 2022)
Background: Study RTOG 9802 in high-risk Diffuse Low-Grade Gliomas (DLGGs) showed the potential synergistic effect on survival of the PCV - radiotherapy (RT) combination. Limited data on long-term neurocognitive impact and quality of life (QoL) have yet been reported.Patients and Methods: We described a monocentric series of patients treated at first line by the combination of PCV immediately followed by RT between 01/01/1982 to 01/01/2017. Radiological data were collected and included volume, velocity of diametric expansion (VDE) and MRI aspects. Long-term neurocognitive and QoL were analyzed. Results: Twenty patients fulfilled the eligibility criteria. The median response rate was 65.1% (range, 9.6 - 99) at the time of maximal VDE decrease corresponding to a median volume reduction of 79.7cc (range, 3.1cc to 174.2 cc), which occurred after a median period of 7.2 years (range, 0.3 - 21.9) after the end of RT. An ongoing negative VDE was measured in 13/16 patients after the end of RT, with a median duration of 6.7 years (range, 9 months - 21.9 years). The median follow-up since radiological diagnosis was 17.5 years (range, 4.8 to 29.5). Estimated median survival was 17.4 years (95%, IC: 12; NR). After a long-term follow-up, substantial neurotoxicity was noticed with dementia in six progression-free patients (30%), leading to ventriculo-peritoneal shunt procedures in three, and premature death in five. Thirteen patients (65%) were unable to work with disability status. Successive longitudinal neurocognitive assessments for living patients showed verbal episodic memory deterioration.Conclusions: PCV - RT combination seems to have an oncological synergy, but also a long-term neurotoxic synergy to consider before initial therapeutic decision.